Mechanistic Insights into Fish Spoilage and Integrated Preservation Technologies - Xuanbo Wang; Zhaozhu Zheng (Applied Sciences)
The global fish industry faces persistent challenges due to the inherent perishability of fish, driven by enzymatic autolysis, lipid oxidation, and microbial proliferation. Although numerous studies have characterized these individual spoilage pathways and evaluated discrete preservation techniques, practitioners still lack a unified, mechanism-based framework that links spoilage chemistry to targeted interventions. This gap prevents the rational selection and optimization of preservation methods. In this review, we first synthesize recent multi-omics and microbiological findings to delineate the molecular drivers of post-harvest fish spoilage. We then critically map a suite of preservation approaches—including low-temperature treatments (refrigeration, super-chilling, freezing), high-pressure processing, modified atmosphere packaging, nanoemulsion and essential-oil coatings, pulsed electric fields, and ozonation—onto the specific mechanisms they mitigate. By comparing efficacy metrics, practical constraints, and emerging innovations, our mechanism-driven roadmap clearly defines the problems we address and offers actionable guidance for developing more effective and sustainable fish preservation strategies.